IMPLEMENTATION OF PROMOTION MIX AT THE SATE JAWA ASLI RESTAURANT - Isnaini Nuzula Agustin; Suryati Suryati (Universitas Internasional Batam, 2022)
The Covid-19 pandemic has had an impact on Micro, Small, and Medium Enterprises (MSMEs). Many MSMEs experienced a decrease in sales and even went out of business. The Sate Jawa Asli Restaurant is one of the MSMEs that experienced a decrease in sales due to lack of visitors. Sate Jawa Asli Restaurant has been registering their business in go food and grab food. In addition, Sate Jawa Asli Restaurant has Instagram but seldom to updates or interacts with Instagram users. So, the promotion mix is ​​implemented in the form of advertising, direct and digital marketing, and sales promotion using Instagram social media. The activities undertaken were content updates, endorsement, and a giveaway. The results of the promotion mix activities were increases in sales and the enhancement of brand awareness. The promotion mix is ​​expected to continuously implemented to maintain the existence and development of Sate Jawa Asli Restaurant.